International Survey of Eye Care Practitioners on Dry Eye Disease: A Comparative Analysis of South Africa, the United Kingdom and Other Global Regions - Christine Croker; Shehzad A. Naroo; Raquel Gil-Cazorla (Journal of Clinical Medicine, 2026)
Background: Dry eye disease (DED) and meibomian gland dysfunction (MGD) impose a significant global burden, yet clinical practice varies substantially between regions. This study investigated international trends in DED diagnosis and management among eye care practitioners (ECPs), with regional focus on South Africa (SA), the United Kingdom (UK) and the rest of the world (RoW; heterogeneous international respondents). Methods: An anonymised cross-sectional online survey was distributed to ECPs globally (May 2023–September 2024). In total, 383 participants from 31 countries were included in the analysis (SA n = 137; UK n = 112; RoW n = 134). Mann–Whitney U tests with Benjamini–Hochberg false discovery rate correction, chi-square tests and Kendall’s tau concordance were applied. Results: SA practitioners reported significantly lower confidence across all four DED domains than their UK and RoW counterparts (all q < 0.05; Cliff’s delta small-to-medium). Core diagnostic practices—case history (88.7%), fluorescein staining (79.4%) and tear break-up time (77.3%)—were globally consistent. UK practitioners showed greater recognition of blepharitis and higher uptake of lid massage, dietary modification and intense pulsed light. Advanced diagnostics received low reported importance globally. Conclusions: Significant regional disparities exist in practitioner confidence, diagnostic emphasis and therapeutic access. A tiered diagnostic framework is proposed to support equitable care, applying a universal core of assessments supplemented by advanced tools where resources permit.